Answer:
Unless the two equations are exactly the same, there can only be one point of intersection.
Answer:
=8
Step-by-step explanation:
The answer is 8 because when you square root 64
f (n + 1) = –3 f(n )
f (n + 1) = 3 f(n )
f (n + 1) = –2 f(n )
f (n + 1) = 2 f(n)
Answer:
, where f(1)=3
Step-by-step explanation:
The given sequence is; 3, –6, 12, –24, 48, …
The first term of this sequence is
There is a common ratio of
We can actually use any other two consecutive terms in the sequence to obtain the common ratio.
The recursive formula is given by:
We plug in the common ratio to get:
, where f(1)=3
Answer:
The answer is C
Step-by-step explanation: